PENGARUH METODE PROBLEM SOLVING TERHADAP KEMAMPUAN SAINS PADA ANAK USIA 5-6 TAHUN DI TK AL-MUNAWARAH KECAMATAN MERBAU TELUK BELITUNG KABUPATEN KEPULAUAN MERANTI - Sutina, Dewi; Indarto, Wusono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aimed to determine whether there are significant implementation problems method solvingpada children aged 5-6 years in tk al-Munawarah districts merbau meranti island district. The research method is observation using observation sheet. Samples were determined in this study were 17 children. Data analysis technique using Wilcoxon test with the help of IBM SPSS Ver.20 Statistick. A significant difference between the methods of problem solving with science abilities of children. It inidapatdiketahuidarihasilanalisa statistical data diperolehtest sign wilcoxon.bahwa results for 0:00 of <0.05. This may imply that there is a difference in the success rate of science abilities of children before and after treatment using the method of problem solving. When in the conference to the Z value is obtained Z count equal to -3.638. engineering problem solving method gives the effect of 29.23 %% the middle category.CateKeywords: Methods of Problem Solving, Science Capabilities